2019
DOI: 10.1097/mej.0000000000000515
|View full text |Cite
|
Sign up to set email alerts
|

Management of anaphylaxis in Spain: pediatric emergency care providers’ knowledge

Abstract: Even though the Spanish pediatric ED providers' knowledge of the management of anaphylaxis is good, certain improvement areas are identified in both the identification and the management of these patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
13
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 17 publications
5
13
0
Order By: Relevance
“…Compared to other authors, we observed that the percentage of prescription of epinephrine ampules or autoinjectors was low. Grossman et al [ 16 ] reported a prescription rate of 98%, although some studies found a percentage similar to ours [ 17 18 ]. One of the possible causes of the low percentage we got is the scarce or nonexistent availability of autoinjectors in our country.…”
Section: Discussionsupporting
confidence: 78%
See 3 more Smart Citations
“…Compared to other authors, we observed that the percentage of prescription of epinephrine ampules or autoinjectors was low. Grossman et al [ 16 ] reported a prescription rate of 98%, although some studies found a percentage similar to ours [ 17 18 ]. One of the possible causes of the low percentage we got is the scarce or nonexistent availability of autoinjectors in our country.…”
Section: Discussionsupporting
confidence: 78%
“…Grossman et al [ 16 ] reported an important percentage of 93.5% use of epinephrine in a survey taken by pediatricians. Surveys taken by physicians report an epinephrine use higher than 75% [ 17 18 23 24 25 26 27 28 29 ]. Moreover, Plumb et al [ 30 ] and Jose and Clesham [ 31 ] reported 100% and 94% use of epinephrine, respectively.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Two different studies ascertained that frequent experience with cases of anaphylaxis and knowledge of the diagnosis criteria of anaphylaxis were predictive factors in determining the first treatment correctly. 19,20 Similarly, our study found that having experience with a case of anaphylaxis (OR:2.4) and additionally having experience with EAIs (OR:5.5) and knowing the administration route of epinephrine correctly (OR:1.9) were significant factors in knowing the first and lifesaving treatment of anaphylaxis correctly.…”
Section: Discussionsupporting
confidence: 56%